IMPACT OF MIDSEASON DROUGHT ON PHYSIOLOGICAL AND BIOCHEMICAL PARAMETERS IN GROUNDNUT - Y. AMARAVATHI (The Journal of Research ANGRAU, 2018)
Drought is one of the important abiotic stresses restricting the productivity of groundnut in rainfed situation by altering physiological and biochemical parameters. The effect of transient water deficit stress on physiological and biochemical parameters like SPAD Chlorophyll Meter Reading (SCMR), the Specific Leaf Area (SLA), proline content, catalase and peroxidase enzymes was analysed during Kharif, 2016 at pegging and pod filling stages in four groundnut genotypes with different levels of drought tolerance under two water regimes viz., field capacity and mid-season drought. The results indicated that SCMR, proline content, catalase and peroxidase levels were increased and SLA decreased significantly in all genotypes at different levels of moisture stress condition when compared to control. Under prolonged drought stress, the increase in proline content is more predominant in drought sensitive genotypes like Kadiri6 and Narayani and is twice as that of drought tolerant genotypes TCGS 1157 and MLTG 4. In contrast, catalase and peroxidase enzymes activity was found to be significantly high in drought tolerant genotypes than in drought sensitive genotypes.The genotypes with high SCMR, peroxidase and catalase activity and low SLA and proline content can tolerate moisture stress and can be used as a basis in development of groudnut genotypes for rainfed condition.